The effect of recompression and concentration of polyvinylpyrrolidone (PVP) K-30 on the quality of paracetamol tablets - Lestari, Agatha Budi Susiana; Angelina, Desak Made Rachel (Pharmaciana, 2024)
Quality control during production is a critical process that ensures the quality of the tablets until it reaches the consumer. In the pharmaceutical industry, there is a possibility of reworking, including tablet recompression. Nevertheless, the recompression process may have affected the potential of PVP K-30 as a binder to reunite the particles of tablet ingredients. However, the difference of PVP K-30 concentration might be resulting in the differences of granule and tablet characteristics. This study aims to determine whether there is an effect of recompression and the difference of PVP K-30 on the quality of paracetamol tablets. The effect of recompression and the difference of PVP K-30 was seen based on whether there is a significant different on physical properties of the mixture of tablet ingredients (mixture’s flow rate and compressibility) and the tablets (compatibility and tablet’s hardness, friability, and disintegration time) from the formula with a concentration of 2% w/w and 4% w/w PVP K-30 after experiencing 2 times of recompression. Paracetamol tablets were made by wet granulation method through the stages of granulation, lubrication, physical properties testing of the mixture, tablet compression, physical properties testing of tablets, crushing, and recompression. Data analysis was performed statistically using the Shapiro-Wilk normality test, followed by two-way Analysis of Variance (ANOVA) or Kruskal-Wallis test and Post Hoc Mann Whitney test. The results showed there was an effect of recompression and different concentration of PVP K-30 on the potential of PVP K-30 as a binder as seen from significant differences in the physical properties of the mixture and tablets in each test group.